Metabolomics analysis reveals the bitter active ingredients in Lonicera caerulea L. - Zhu, Ling; Zhang, Xindi; Han, Yaxi; Wang, Kunlun; Yao, Xinmiao; Zhou, Ye; Li, Bo; Ji, Nina; Lu, Shuwen; Guan, Lijun (Frontiers in Nutrition, 2025)
IntroductionBlue honeysuckle (Lonicera caerulea L.) is a nutritionally valuable cold-climate berry characterized by a considerable bitter taste. While bitter compounds in plant foods are often associated with favorable physiological activities, their specific identities in blue honeysuckle remain unclear.MethodsThis study combined sensory evaluation, electronic tongue analysis, and untargeted metabolomics based on ultra-performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) to identify and compare bitter compounds in three cultivars of blue honeysuckle.ResultsA total of 73 bitter metabolites were identified in blue honeysuckle, predominantly flavonoids, amino acids and derivatives, phenolic acids, lipids, and tannins. The highest-bitterness variety, Chaoxian (CX) exhibited specific accumulation of l-valine, l-leucine, l-histidine, l-phenylalanine, eriodictyol, trifolin, isoorientin, naringin, and eriocitrin compared to Luohuotan (LHT) and Lanjingling (LJL). The KEGG enrichment analysis implicated the biosynthesis of amino acids (ko01230) and flavonoid biosynthesis (ko00941) as primary contributors to inter-varietal bitterness divergence.DiscussionThese findings provide important information for retaining bioactive bitter metabolites in blue honeysuckle and optimizing its flavor profile to enhance market acceptability.